-- | Useful List operations, part of the "Useful" module. module Useful.List where import Useful.General import Data.List -- | Takes a list item and splits a list around it, removing the item. -- -- > $ explodeI "Hello there people" ' ' -- > ["Hello","there","people"] explodeI :: Eq a => [a] -> a -> [[a]] explodeI xs m = rmEmptyList (explode' xs m) -- explode' :: Eq a => [a] -> a -> [[a]] explode' [] m = [] explode' xs m = [takeWhile (!=m) xs] ++ explode' (tail' (dropWhile (!=m) xs)) m where tail' [] = [] tail' (x:xs) = xs -- | Alias of explodeI splitI :: Eq a => [a] -> a -> [[a]] splitI = explodeI -- | Take a list item and concatinates each element of it around another given item. -- -- > $implodeI "askjdnaskd" '!' -- > "a!s!k!j!d!n!a!s!k!d" implodeI :: Eq a => [a] -> a -> [a] implodeI (x:xs) y |xs == [] = [x] |otherwise = (x : [y]) ++ (implodeI xs y) -- | alias of implodeI joinI :: Eq a => [a] -> a -> [a] joinI = implodeI -- | Takes a two lists and explodes the first into a new list, around the second. Removing the second list where it occurs. -- -- THIS NEEDS FIXING explode :: Eq a => [a] -> [a] -> [[a]] explode x y = explode'' x y 0 0 -- explode'' :: Eq a => [a] -> [a] -> Int -> Int -> [[a]] explode'' x y buff count |x == y = [] |x == [] = [] |y == [] = [x] |buff == len y = (takeBefore buff (fst splut)) : ( explode'' (snd splut) y 0 0) -- If the buffer is full (match found). Then split and remove match from fst, cons onto the explode'' of the second part. |(len x < count) && ((x !! count) ? y) = explode'' x y (((x !! count) ?! y )+1) (count+1) -- is x !! count in y? If so then find at which position and explode'' with that +1 as the new buffer. |otherwise = explode'' x y 0 (count+1) -- otherwise increment the counter. where splut = (splitAt count x) -- | alias of explode split :: Eq a => [a] -> [a] -> [[a]] split = explode -- | Takes a list of lists and an extra list and concatinates the list of lists with the second list inbetween. When used with the empty list mimics concat -- -- > $ implode ["helloasdad","asd hello","hello"] "!!" -- > "helloasdad!!asd hello!!hello" implode :: Eq a => [[a]] -> [a] -> [a] implode x [] = concat x implode (x:xs) y |xs == [] = x |otherwise = (x ++ y) ++ (implode xs y) -- | Alias of implode join :: Eq a => [[a]] -> [a] -> [a] join = implode -- | takes n number of items from the front of a list -- -- > $ takeFor 5 "Hello there people" -- > "Hello" takeFor :: Eq a => Int -> [a] -> [a] takeFor n x = takeFor' n x 0 takeFor' n (x:xs) c |xs == [] = x: [] |c == n = [] |otherwise = x : takeFor' n xs (c+1) -- | drops n number of items from the front of a list -- -- > $ dropFor 5 "Hello there people" -- > " there people" dropFor :: Eq a => Int -> [a] -> [a] dropFor n x = dropFor' n x 0 dropFor' n (x:xs) c |(xs == []) && (c <= n) = [] |(xs == []) && (c > n) = (x:xs) |c < n = [] ++ dropFor' n xs (c+1) |otherwise = x : dropFor' n xs (c+1) -- | takes a number of items from a list before it reaches the index n -- -- > $ takeBefore 5 "Hello there people" -- > "Hello there p" takeBefore :: Eq a => Int -> [a] -> [a] takeBefore n x = takeFor' (len x - n) x 0 -- | drops a number of items from a list before it reaches the index n -- -- > $ dropBefore 5 "Hello there people" -- > "eople" dropBefore :: Eq a => Int -> [a] -> [a] dropBefore n x = dropFor' (len x - n) x 0 -- | In a list of lists this removes any occurances of the empty list. Can also be used to remove occurances of the empty string. rmEmptyList :: Eq a => [[a]] -> [[a]] rmEmptyList [] = [] rmEmptyList (x:xs) |x == [] = rmEmptyList xs |otherwise = x:(rmEmptyList xs) -- | maps a function in depth N to the given list. map3, map4, map5 are also defined. -- -- > $ map2 (*2) [[1,2,3,4],[1,1,1,2]] -- > [[2,4,6,8],[2,2,2,4]] map2 :: (a -> b) -> [[a]] -> [[b]] map2 f x = map (map f) x map3 f x = map (map (map f)) x map4 f x = map (map (map (map f))) x map5 f x = map (map (map (map (map f)))) x -- | returns a list of size n filled with items x -- -- > $ initList 0 5 -- > [0,0,0,0,0] initList :: a -> Int -> [a] initList x 0 = [] initList x n = x : (initList x (n-1)) -- | Replaces any occuranses of the second list, with the third list, in the first list. -- -- > $ replace "why hello hello there" "hello" "bonjour" -- > "why bonjour bonjour there" replace :: Eq a => [a] -> [a] -> [a] -> [a] replace s [] x = s replace [] _ _ = [] replace s find repl |take (length find) s == find = repl ++ (replace (drop (length find) s) find repl) |otherwise = [head s] ++ (replace (tail s) find repl) -- | Takes a list of items and returns a list with each element in it's own single list. -- -- > $ each "hello" -- > ["h","e","l","l","o"] each :: [a] -> [[a]] each x = f x where f :: [a] -> [[a]] f [] = [] f (x:xs) = [x] : f xs